DEVELOPMENT OF THE GRACEFUL AGEING MODULE TO INCREASE PSYCHOLOGICAL WELL-BEING AMONGST OLDER ADULTS IN MALAYSIA - Thiyagarajan, Ahsha Vaksalla; Amit, Noh; Ghazali, Shazli Ezzat; Siau, Ching Sin; Chan, Caryn Mei Hsien; Ibrahim, Norhayati; Subramaniam, Ponnusamy (Malaysian Journal of Public Health Medicine, 2023)
Population ageing is a worldwide phenomenon. Interventions to accommodate the needs of the ageing population is essential. This study aims to describe the development of the Graceful Ageing Module, which was designed for older adults aged 60 and above to enable graceful ageing from different positive perspectives. The Graceful Ageing Module was developed based on Sidek’s Module Development Model. The basis for developing this module was based on previous intervention studies designed for older adults, which were identified through previous studies on older adults in Malaysia. The topics in the module consisted of 1. Remembering well; 2. Reconstruction; 3. A better life is in my hands; 4. The grace and strength within me; 5. Psychological well-being; 6. Ageing gracefully, positively and productively; and 7. My social support & networking. This study employed quantitative and qualitative designs. The results showed that the content validity evaluation was conducted by a panel of experts and geriatric participants. Krippendorff’s interval alpha was used to determine the content validity based on the panel’s feedback. During the content validation stage, the reviewers, consisting of 11 experts, identified the strengths and weaknesses of the module and revisions were made, such as adjusting the duration and content of the module. Krippendoff’s interval alpha was 0.98, which indicated a high degree of reliability with almost perfect agreement. In conclusion, the Graceful Ageing Module was found to have high content validity and is ready to be tested amongst older adults in Malaysia. Implications for various stakeholders are discussed.